Advances in research on the carrot, an important root vegetable in the Apiaceae family. Issue 1 (1st June 2019) - Que, Feng; Hou, Xi-Lin; Wang, Guang-Long; Xu, Zhi-Sheng; Tan, Guo-Fei; Li, Tong; Wang, Ya-Hui; Khadr, Ahmed; Xiong, Ai-Sheng
Abstract: Carrots ( Daucus carota L.), among the most important root vegetables in the Apiaceae family, are cultivated worldwide. The storage root is widely utilized due to its richness in carotenoids, anthocyanins, dietary fiber, vitamins and other nutrients. Carrot extracts, which serve as sources of antioxidants, have important functions in preventing many diseases. The biosynthesis, metabolism, and medicinal properties of carotenoids in carrots have been widely studied. Research on hormone regulation in the growth and development of carrots has also been widely performed. Recently, with the development of high-throughput sequencing technology, many efficient tools have been adopted in carrot research. A large amount of sequence data has been produced and applied to improve carrot breeding. A genome editing system based on CRISPR/Cas9 was also constructed for carrot research. In this review, we will briefly summarize the origins, genetic breeding, resistance breeding, genome editing, omics research, hormone regulation, and nutritional composition of carrots. Perspectives about future research work on carrots are also briefly provided. Carrots: past and future: China accounts for nearly half of the total global production of carrots and advances in genetic technologies are contributing to improve both crop quality and yield. Cultivated carrot is the second most popular vegetable in the world after potato; this can be largely attributed to their taste and their nutritional benefits. Ai-Sheng Xiong and colleagues at Nanjing Agricultural University, China, review the latest studies on the origin and breeding of carrots. Understanding the genetic sequence and gene expression patterns in carrot plants provides valuable insights into their evolution as well as into the mechanisms underlying their resistance to disease, production of healthy carotenoids and environmental stress tolerance. Future application of gene editing technologies will help to further improve crop production and the nutritional value of carrots.